A foamed slurry composition, foamed coating and fabric
Patent Information
- Application Number
- CN202611218216.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-16
AI Technical Summary
但目前的发泡材料一般都是较为均匀的硬度,不同位置的硬度差别较小,而在一些应用场景上需要发泡材料在不同区域具有不同的硬度,比如应用于鞋材面料上时,曲面位置可能会要求发泡材料的边缘区域硬度较高、中间区域硬度较低
(1)本发明的发泡浆料组合物中采用解封温度(T3)相对较低的封闭型异氰酸酯固化剂可以在局部区域产生解交联(解封后交联)并形成较为一定交联度的交联结构;水性树脂具有自交联作用,可以在加热(温度T1)下在异氰酸酯固化剂解封后形成的交联结构基础上继续发生交联,获得高交联度的交联结构;随着温度升高至T2或更高,发泡剂发生膨胀或产生气体进行发泡,但致密交联结构的区域抑制发泡,交联密度低的区域来不及继续发生交联或交联密度较低,可以明显发泡,从而通过调整不同区域的交联致密性和发泡程度,获得不同区域具有不同硬度的发泡材料。
Smart Images

Figure CN122917657A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of foaming material technology, and relates to a foaming slurry composition, a foaming coating, and a fabric. Background Technology
[0002] Foamed materials have been widely used in various applications, such as foam coatings on fabric surfaces, which can provide decoration, protection, and other functions. However, current foamed materials generally have relatively uniform hardness, with little difference in hardness across different locations. In some applications, however, different hardness levels are required in different areas of the foamed material. For example, when used in shoe uppers, curved surfaces may require higher hardness at the edges and lower hardness in the center. However, there are currently few reports on foamed materials with varying hardness in different areas. Summary of the Invention
[0003] To address the aforementioned technical problems, the present invention provides a foaming slurry composition, a foaming coating, and a fabric.
[0004] The technical solution of the present invention is as follows:
[0005] A foaming slurry composition, by 100% weight, comprises: 40-65% aqueous resin emulsion, 1-5% foaming agent, 0.5-2% thickener, 0.1-1% defoamer, 0.2-1% dispersant, 2-8% blocked isocyanate curing agent, and the balance being solvent; The aqueous resin emulsion is selected from one or both of self-crosslinking acrylic resin emulsion and self-crosslinking polyurethane emulsion, and the hydroxyl value of the resin in the aqueous resin emulsion is 50-120 mgKOH / g. The thermal activation temperature of the aqueous resin emulsion is T1, the foaming temperature of the foaming agent is T2, and the unsealing temperature of the blocked isocyanate curing agent is T3, then T2 > T1 > T3.
[0006] Preferably, T1, T2 and T3 satisfy: T2≥T1+10, T1≥T3+10.
[0007] More preferably, T1 is 110-135℃, T2 is not lower than 120℃, and T3 is 60-110℃.
[0008] More preferably, the temperature of T2 does not exceed 180°C; The foaming agent is selected from either physical foaming agents or chemical foaming agents.
[0009] Preferably, the physical foaming agent is selected from expanded microspheres; The chemical foaming agent is selected from foaming agent AC and / or foaming agent H; The chemical foaming agent also contains an activator.
[0010] Preferably, the solvent is selected from one or two of water and ether-based organic solvents; The raw material components also include: 5-20% inorganic filler.
[0011] A foamed coating, comprising the steps of: S1. The foaming slurry composition described in any of the above embodiments is applied as a coating and pre-dried at a temperature below T3 to obtain a pre-dried coating; S2. The local area of the pre-dried coating described in step S1 is heated to a temperature not lower than T3 but lower than T1, and cross-linking and curing occur at the local area. S3. Continue to heat the local area mentioned in step S2 to a temperature not lower than T1 but lower than T2, and continue to cross-link and solidify the local area. Then, heat the area to a temperature not lower than T2 to foam and obtain the foamed coating.
[0012] Preferably, the foaming coating consists of several sub-coatings, wherein the weight percentage of the foaming agent in the several sub-coatings is equal, or the gradient increases or decreases.
[0013] More preferably, the foaming slurry composition is applied to the surface of the fabric, and the weight percentage of the foaming agent in the plurality of sub-coatings increases in a gradient starting from the surface.
[0014] A fabric comprising a base fabric and a printed coating located on one or both sides of the base fabric; The printed coating is prepared from or comprises the foamed slurry composition described in any of the above embodiments.
[0015] The beneficial effects of this invention are: (1) In the foaming slurry composition of the present invention, the closed isocyanate curing agent with a relatively low unblocking temperature (T3) can produce de-crosslinking (crosslinking after unblocking) in local areas and form a crosslinking structure with a certain degree of crosslinking; the waterborne resin has a self-crosslinking effect and can continue to crosslink on the basis of the crosslinking structure formed after the isocyanate curing agent is unblocked under heating (temperature T1) to obtain a crosslinking structure with a high degree of crosslinking; as the temperature rises to T2 or higher, the foaming agent expands or generates gas to foam, but the area with dense crosslinking structure inhibits foaming, while the area with low crosslinking density does not have time to continue crosslinking or has a low crosslinking density and can foam significantly. Thus, by adjusting the crosslinking density and foaming degree of different areas, foaming materials with different hardness in different areas can be obtained.
[0016] (2) The foam coating of the present invention has different hardness in different areas, which can be applied to fabrics, improving the diversity of fabric foam coatings and broadening the application field of fabrics. Attached Figure Description
[0017] Figure 1 This is a photograph of the actual appearance of the foamed coating obtained in Example 1; Among them, 1-edge region, 2-middle region, 3-transition region. Detailed Implementation
[0018] The technical solution of the present invention will be further explained and described below through specific embodiments.
[0019] This invention proposes a foaming slurry composition, which, by 100% weight, comprises: 40-65% aqueous resin emulsion, 1-5% foaming agent, 0.5-2% thickener, 0.1-1% defoamer, 0.2-1% dispersant, 2-8% blocked isocyanate curing agent, and the balance being solvent; The aqueous resin emulsion is selected from one or both of self-crosslinking acrylic resin emulsion and self-crosslinking polyurethane emulsion, and the hydroxyl value of the resin in the aqueous resin emulsion is 50-120 mg KOH / g. The thermal activation temperature of the waterborne resin emulsion is T1, the foaming temperature of the foaming agent is T2, and the unblocking temperature of the blocked isocyanate curing agent is T3. Therefore, T2 > T1 > T3.
[0020] In this invention, a resin emulsion with self-crosslinking properties is used as a binder, exhibiting three different temperature effects: the thermal activation temperature T1 of the aqueous resin emulsion, the foaming temperature T2 of the foaming agent, and the desealing temperature T3 of the blocked isocyanate curing agent, with T2 > T1 > T3. As the temperature rises, the desealing temperature T3 of the blocked isocyanate curing agent is reached first, causing it to deseale and produce a certain degree of crosslinking in localized areas of the aqueous resin. With continued heating, the thermal activation temperature T1 of the aqueous resin emulsion is reached again, and the aqueous resin continues to produce a certain degree of self-crosslinking in localized areas, resulting in a high degree of crosslinking in localized regions. With further heating, when the foaming temperature T2 of the foaming agent is reached, the foaming agent foams rapidly. The curing agent and self-crosslinking resin that have not yet produced crosslinking do not have enough time to achieve a high degree of crosslinking (e.g., in the middle region). Areas with low crosslinking degree exhibit high foaming, while areas with high crosslinking degree exhibit low foaming or even no foaming, thus forming a foamed material with different hardness and foaming degrees in different regions. During the heating stages T3 and T1, different regions of the crosslinked coating exhibit varying degrees of crosslinking. For example, the central region has a low degree of crosslinking, while the edge regions have a high degree of crosslinking. When the temperature is further increased to T2 or higher for foaming, different regions will produce different degrees of foaming. The edge regions, with their high degree of crosslinking (dense crosslinked structure, high hardness), exhibit low or no foaming due to the inhibitory effect of the high crosslinking density on foaming expansion. Conversely, the central regions, with their low degree of crosslinking (loose crosslinked structure, low hardness), show less inhibition of foaming expansion and exhibit high foaming. The lower the degree of foaming, the higher the hardness, further widening the hardness difference between the high and low degree foaming regions, thus achieving different hardnesses in different areas of the coating.
[0021] In this invention, there are no particular limitations on the blocked isocyanate curing agent; it can be a water-based blocked isocyanate curing agent. There are no particular limitations on the water-based resin emulsion; it can be directly obtained from the market, for example, it can be the water-based acrylic emulsion Valbond 8445E.
[0022] In some embodiments, T1, T2, and T3 satisfy: T2 ≥ T1 + 10, T1 ≥ T3 + 10. When there is a certain temperature interval between T3 and T1, and a certain temperature interval between T1 and T2, such as 10°C or above, the heating effect in different temperature ranges can be better achieved. For example, at T3, the locally blocked isocyanate curing agent is desealed by heat and crosslinks the waterborne resin at that location, forming a certain degree of crosslinking.
[0023] In some embodiments, T1 is 110-135℃, T2 is not lower than 120℃, and T3 is 60-110℃. For example, when T3 is 60℃, T1 can be 110℃, 120℃, 130℃, 135℃, etc.; when T3 is 110℃, T1 can be 120℃, 130℃, 135℃, etc.; when T1 is 110℃, T2 can be 120℃, 130℃, 135℃, 140℃, 145℃, 150℃, 160℃, etc.; when T1 is 135℃, T2 can be 145℃, 150℃, 160℃, 165℃, etc. Furthermore, T2 is not lower than 140℃.
[0024] In some embodiments, T2 does not exceed 180°C; The foaming agent is selected from either physical foaming agents or chemical foaming agents.
[0025] In some preferred embodiments, the physical foaming agent is selected from expanded microspheres; The chemical foaming agent is selected from foaming agent AC and / or foaming agent H.
[0026] In this invention, the foaming agent can be a physical foaming agent or a chemical foaming agent. When a physical foaming agent is used, the foaming agent can be expanded microspheres (in their unexpanded state). Expanded microspheres can be directly obtained from the market and selected according to different expansion temperatures, such as expanded microspheres with an expansion temperature of 140-150℃, such as the physical foaming agents HY-160D and HY-180D from Shenzhen Heyan Yuese Plastic Pigment Additives Co., Ltd., the thermally expanded microspheres from Hangzhou Yingxing New Materials Co., Ltd., and the foaming agent EM406 from SEKISUI of Japan. The foaming agent of this invention can also be a chemical foaming agent, such as foaming agent AC and foaming agent H. Chemical foaming agents also contain activators, such as zinc oxide and zinc stearate, which can adjust the foaming temperature to 160-180℃.
[0027] Setting the foaming temperature T2 to no more than 180℃ can avoid the adverse effects of excessively high temperatures on the coating, such as thermal aging.
[0028] In some embodiments, the solvent is selected from one or both of water and ether-based organic solvents; The raw material components also include: 5-20% inorganic filler.
[0029] In this invention, water and / or ether-based organic solvents can be used as diluents in the foaming slurry composition. Ether-based organic solvents can be ethylene glycol dimethyl ether, propylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, etc.
[0030] The inorganic filler is not particularly limited and can be hollow glass microspheres, light calcium carbonate, kaolin, etc. The thickener is not particularly limited in this invention; for example, it can be a polyurethane-associated thickener, organobentonite, or fumed silica. The defoamer is not particularly limited; for example, it can be a dimethyl silicone oil defoamer. The dispersant is not particularly limited; for example, it can be a polycarboxylate dispersant, such as 5040, SN-5040, 1620, 1618, etc.
[0031] There are no particular limitations on the preparation method of the foaming slurry composition of the present invention; it is sufficient to mix and stir the raw material components to disperse them evenly.
[0032] On the other hand, the present invention also proposes a foamed coating, the steps of which include: S1. The foaming slurry composition described in any of the above embodiments is applied as a coating and pre-dried at a temperature below T3 to obtain a pre-dried coating; S2. Local areas of the pre-dried coating in step S1 are heated to a temperature not lower than T3 but lower than T1, and cross-linking and curing occur in the local areas. S3. Continue to heat the local area in step S1 to a temperature not lower than T1 but lower than T2, and continue to cross-link and cure the pre-dried local area. Then heat it to a temperature not lower than T2 to foam and obtain a foamed coating.
[0033] In this invention, the foaming slurry composition exhibits crosslinking at two temperature ranges. The first temperature range is the unblocking temperature T3 of the blocked isocyanate curing agent, and the second temperature range is the thermal activation temperature T1 of the waterborne resin emulsion. The degree of crosslinking differs between the two temperature ranges, with the degree of crosslinking at T3 being significantly greater than that at T1. When a localized area (e.g., the middle region) of the pre-dried coating (pre-dried below T3, such as 50°C or 55°C) is shielded (e.g., with aluminum foil), the unshielded area (e.g., the edge region) is heated with an infrared lamp to reach the unblocking temperature T3 of the blocked isocyanate curing agent. In this case, the blocked isocyanate curing agent in the edge region unblocks and crosslinks the waterborne resin in that area. However, the waterborne resin in the middle region does not reach T3 and does not undergo crosslinking. When the temperature at the edge region continues to rise to the thermal activation temperature T1 (or appropriately higher), crosslinking continues to occur in the edge region. The process involves creating a cross-linked structure and achieving a high cross-linking density. However, the cross-linking density in the central region is very low, or even nonexistent. The temperature is then raised to the foaming temperature T2 (or appropriately higher). Due to the high cross-linking density, the edge region cannot foam or foams very little, while the central region, with its low cross-linking density, foams significantly. Because of the limited foaming time, the central region does not have enough time to achieve a high cross-linking density, resulting in a foamed coating with varying hardness in different areas: the edge region has high hardness (high cross-linking density, low foaming degree), and the central region has low hardness (low cross-linking density, high foaming degree). In step S2, localized areas (such as the edge region) undergo cross-linking and curing. The transition zone between the edge and central regions may also experience a temperature increase due to heating radiation from the edge region, and may also exhibit some cross-linking, resulting in a lower hardness in the transition zone compared to the edge region, but a higher hardness in the central region.
[0034] In some embodiments, the coating consists of several sub-coatings, in which the weight percentage of foaming agent is equal, or the gradient increases or decreases. For example, the coating consists of three sub-coatings, which are, from bottom to top, a bottom coating, an intermediate coating, and a top coating. The bottom coating contains 1-2 wt% foaming agent, the intermediate coating contains 3 wt% foaming agent, and the top coating contains 4-5 wt% foaming agent, thereby resulting in different degrees of foaming and different hardness among the sub-coatings.
[0035] In some embodiments, the foaming paste composition is applied to the surface of the fabric, and the weight percentage of the foaming agent in several sub-coatings gradually increases from the surface. That is, the sub-coating in contact with the fabric has the lowest foaming agent content and the lowest degree of foaming, avoiding poor adhesion between the coating and the fabric due to high foaming.
[0036] In another aspect, the present invention also proposes a fabric comprising a base fabric and a printed coating located on one or both sides of the base fabric. The printed coating is prepared from or comprises the foamed paste composition described in any of the above embodiments.
[0037] The foamed coating on the fabric has different hardness in different areas, that is, the hardness is uneven, which improves the versatility of the fabric in protective applications.
[0038] The technical solution of the present invention will be further described and illustrated below with reference to various embodiments. Unless otherwise specified, the parts mentioned in the following embodiments are parts by weight.
[0039] Example 1 The foaming slurry composition, by 100% weight, comprises: 60% self-crosslinking acrylic resin emulsion (solid content 55%, resin hydroxyl value 80mgKOH / g), 3% expanded microspheres, 1% polyurethane associative thickener, 0.4% dimethyl silicone oil defoamer, 0.6% polycarboxylate dispersant, 3% blocked isocyanate curing agent, and the balance being water.
[0040] The thermal activation temperature of the self-crosslinking acrylic resin emulsion is 120℃, the initial foaming temperature of the expanded microspheres is 145℃, and the deblocking temperature of the blocked isocyanate curing agent is 80℃.
[0041] The foaming paste composition was applied to the fabric surface by screen printing, with a coating thickness of 500 μm. It was then pre-dried by heating at 60°C for 1 hour to obtain a pre-dried coating.
[0042] The middle area of the pre-dried coating is covered with aluminum foil, while the edge area is exposed. The edge area is irradiated with an infrared lamp, and the edge area is heated to 85°C and maintained for 20 minutes. The edge area is then irradiated with an infrared lamp to raise the temperature to 127°C and baked at a constant temperature for 30 minutes. The aluminum foil is then removed, and the coating is irradiated with an infrared lamp to raise the temperature to 145°C and baked for another 2 minutes. The expanded microspheres expand, and a foamed coating is obtained.
[0043] The actual appearance of the foamed coating in this embodiment is shown in the attached image. Figure 1 As shown, edge region 1 has virtually no foaming, while the middle region 2 exhibits significant foaming and expansion. A transition zone 3 exists between edge region 1 and the middle region 2, and while transition zone 3 also shows foaming, its degree of foaming is lower than that of the middle region 2. The Shore hardness of the edge region was measured to be 55D, the middle region 20D, and the transition zone 40D (due to the softness of the fabric, the hardness test was performed by applying the foaming slurry composition to a clean tinplate surface). Therefore, the hardness of the foamed coating obtained in this embodiment is uneven, with the edge region exhibiting high hardness and virtually no foaming, while the middle region has low hardness and significant foaming.
[0044] Example 2 The difference between this embodiment and Embodiment 1 is that in Embodiment 1, the weight content of the expanded microspheres was adjusted from 3% to 1%, and the amount of water was increased proportionally. The remaining steps remained unchanged.
[0045] The Shore hardness of the foamed coating in this embodiment was measured to be 55D at the edge region, 30D at the middle region, and 38D at the transition region between the edge and middle regions.
[0046] Comparative Example 1 The difference between this comparative example and Example 1 is that in Example 1, the aluminum foil was removed from the middle area of the pre-dried coating, meaning that the middle area of the pre-dried coating in this comparative example was not covered. The entire pre-dried coating was irradiated with an infrared lamp, and the entire pre-dried coating was heated to 85°C and maintained for 20 minutes. The remaining steps remained unchanged.
[0047] Compared with the hardness of the foamed coating in Example 1, the Shore hardness of the foamed coating obtained in this comparative example is 55D in the edge region, 54D in the middle region, and 55D in the transition region. Therefore, the foamed coating in this comparative example does not have uneven hardness.
[0048] Comparative Example 2 The difference between this comparative example and Example 1 is as follows: In Example 1, the edge area was heated to 85°C and maintained for 20 minutes before the aluminum foil was removed, and then the entire coating was irradiated with an infrared lamp to raise the temperature to 127°C and baked at that temperature for 30 minutes. The remaining steps remained unchanged.
[0049] Compared with the hardness of the foamed coating in Example 1, the Shore hardness of the foamed coating obtained in this comparative example is 55D in the edge region, 52D in the middle region, and 55D in the transition region. Therefore, the non-uniformity of hardness of the foamed coating in this comparative example is not very obvious.
[0050] Comparative Example 3 The difference between this comparative example and Example 1 is that in Example 1, the self-crosslinking acrylic resin emulsion was replaced with a conventional acrylic resin emulsion (solid content 55%, resin hydroxyl value 80 mg KOH / g, which does not have self-crosslinking properties and can only crosslink under the action of a curing agent). The remaining steps remain unchanged.
[0051] In this comparative example, the Shore hardness of the foamed coating's edge region is 32D, the Shore hardness of the middle region is 25D, and the Shore hardness of the transition zone between the edge and middle regions is 28D. Therefore, compared to Example 1, this comparative example only exhibits one type of crosslinking effect—the crosslinking of the acrylic resin by the isocyanate curing agent. The crosslinking density is low, and the crosslinking degree in the first-cured edge region is insufficient to suppress the foaming of the foaming agent, resulting in significant foaming at the edge. Consequently, the reduced crosslinking density in the edge region leads to further foaming, resulting in a significant decrease in the hardness of the edge region. Simultaneously, the Shore hardness of the middle region is also reduced. This may be because, at the temperature at which the expanded microspheres expand, the curing rate of the self-crosslinking acrylic resin is faster than the curing rate of the acrylic resin by the isocyanate curing agent. Therefore, in this comparative example, there is no self-crosslinking of the acrylic resin, resulting in slower crosslinking and a lower degree of crosslinking at the expansion temperature, leading to a lower Shore hardness in the middle region.
[0052] Example 3 The foaming slurry composition, by 100% weight, comprises: 55% of the self-crosslinking acrylic resin emulsion from Example 1, 5% of foaming agent AC, 1.5% of zinc oxide, 1.2% of polyurethane associative thickener, 0.5% of dimethyl silicone oil defoamer, 0.7% of polycarboxylate dispersant, 5% of blocked isocyanate curing agent, and the balance being water.
[0053] The foaming temperature of foaming agent AC is 170℃, and the unsealing temperature of the blocked isocyanate curing agent is 70℃.
[0054] The foaming paste composition was applied to the fabric surface by screen printing, with a coating thickness of 500 μm. It was then pre-dried by heating at 55°C for 1 hour to obtain a pre-dried coating.
[0055] The edge area of the pre-dried coating is covered with aluminum foil, while the middle area is exposed. The middle area is irradiated with an infrared lamp, heated to 72°C and maintained for 30 minutes. The middle area is then irradiated with an infrared lamp to raise the temperature to 125°C and baked at a constant temperature for 30 minutes. The aluminum foil is removed, and the temperature is raised to 175°C and baked for another 5 minutes to foam, thus obtaining a foamed coating.
[0056] The Shore hardness of the foamed coating in this embodiment was measured to be 60D in the middle region, 10D in the edge region, and 31D in the transition region between the edge and middle regions. Therefore, the hardness of the foamed coating obtained in this embodiment is uneven, with high hardness in the middle region and low hardness in the edge region.
[0057] As described above, the basic principles, main features, and advantages of the present invention have been shown and described. Those skilled in the art should understand that the present invention is not limited to the above embodiments, which are merely preferred embodiments and should not be construed as limiting the scope of the invention. All equivalent changes and modifications made in accordance with the scope of the patent and the description should still fall within the scope of the present invention. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A foaming slurry composition, characterized in that, By weight, the raw material composition includes: 40-65% water-based resin emulsion, 1-5% foaming agent, 0.5-2% thickener, 0.1-1% defoamer, 0.2-1% dispersant, 2-8% blocked isocyanate curing agent, and the balance is solvent; The aqueous resin emulsion is selected from one or both of self-crosslinking acrylic resin emulsion and self-crosslinking polyurethane emulsion, and the hydroxyl value of the resin in the aqueous resin emulsion is 50-120 mgKOH / g. The thermal activation temperature of the aqueous resin emulsion is T1, the foaming temperature of the foaming agent is T2, and the unsealing temperature of the blocked isocyanate curing agent is T3, then T2 > T1 > T3.
2. The foaming slurry composition according to claim 1, characterized in that, The conditions T1, T2, and T3 satisfy: T2≥T1+10, T1≥T3+10.
3. The foaming slurry composition according to claim 2, characterized in that, The temperature T1 is 110-135℃, the temperature T2 is not lower than 120℃, and the temperature T3 is 60-110℃.
4. The foaming slurry composition according to claim 3, characterized in that, The temperature T2 shall not exceed 180°C; The foaming agent is selected from either physical foaming agents or chemical foaming agents.
5. The foaming slurry composition according to claim 1, characterized in that, The physical foaming agent is selected from expanded microspheres; The chemical foaming agent is selected from foaming agent AC and / or foaming agent H; The chemical foaming agent also contains an activator.
6. The foaming slurry composition according to claim 1, characterized in that, The solvent is selected from one or two of water and ether-based organic solvents; The raw material components also include: 5-20% inorganic filler.
7. A foamed coating, characterized in that, step include: S1. The foaming slurry composition according to any one of claims 1-6 is applied as a coating and pre-dried at a temperature below T3 to obtain a pre-dried coating; S2. The local area of the pre-dried coating described in step S1 is heated to a temperature not lower than T3 but lower than T1, and cross-linking and curing occur at the local area. S3. Continue to heat the local area mentioned in step S2 to a temperature not lower than T1 but lower than T2, and continue to cross-link and cure the local area. Heat the entire coating to a temperature not lower than T2 to foam, and obtain the foamed coating.
8. The foamed coating according to claim 7, characterized in that, The foaming coating consists of several sub-coatings, wherein the weight percentage of the foaming agent in the several sub-coatings is equal, or the gradient increases or decreases.
9. The foamed coating according to claim 8, characterized in that, The foaming slurry composition is applied to the surface of the fabric, and the weight percentage of the foaming agent in the plurality of sub-coatings increases in a gradient starting from the surface.
10. A fabric, characterized in that, It includes a base fabric and a printed coating located on one or both sides of the base fabric; The printed coating is prepared from the foaming paste composition according to any one of claims 1-6 or includes the foaming coating according to any one of claims 7-9.